2014
DOI: 10.1097/brs.0000000000000073
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal Balance and Spinopelvic Parameters After Lateral Lumbar Interbody Fusion for Degenerative Scoliosis

Abstract: Study Design Retrospective matched–cohort analysis. Objective To evaluate the change in radiographic parameters in patients undergoing interbody fusion and posterior instrumentation compared to posterior spine fusion alone (PSF) for degenerative scoliosis. Summary of Background Data Little is known about the effect of lateral interbody fusion (LIF) on sagittal plane correction in the setting of degenerative scoliosis. We performed a retrospective study to investigate these changes compared to PSF. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 26 publications
3
53
1
1
Order By: Relevance
“…2 Lateral interbody fusion techniques have been shown to yield higher fusion rates and improvement in lumbar lordosis as well as less morbidity than conventional anterior and posterior approaches. 3,4 Sagittal balance is the center-of-mass vector of the spine determined by the reciprocal curves of thoracic kyphosis and lumbar lordosis. Restoration of sagittal balance has repeatedly been shown to portend superior outcomes in pain, function, and health-related quality of life following spine surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Lateral interbody fusion techniques have been shown to yield higher fusion rates and improvement in lumbar lordosis as well as less morbidity than conventional anterior and posterior approaches. 3,4 Sagittal balance is the center-of-mass vector of the spine determined by the reciprocal curves of thoracic kyphosis and lumbar lordosis. Restoration of sagittal balance has repeatedly been shown to portend superior outcomes in pain, function, and health-related quality of life following spine surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Restoration of sagittal balance has repeatedly been shown to portend superior outcomes in pain, function, and health-related quality of life following spine surgery. 3,5 Interbody cages (synthetic implanted scaffolding into the disc spaces) are designed to re-create the natural lordosis of the lumbar spine that is frequently changed by the asymmetric degeneration of the discs and to normalize the overall sagittal balance of the spine.…”
Section: Introductionmentioning
confidence: 99%
“…17,27,68,81 A number of studies have demonstrated the use of standard LLIF in the correction of mild sagittal-and coronal-plane deformities. 1,2,7,15,23,24,27,37,48,56,57,62 More advanced techniques involving the use of hyperlordotic cages with anterior longitudinal ligament (ALL) release and anterior column realignment (ACR) via a lateral technique allow for a significant gain in LL with the added benefit of coronal balance restoration and indirect neuroforaminal decompression at multiple levels in a single procedure. 11,14,41,46,47,52,71,75 Here we compare our series of patients undergoing PSO or multiple-level LLIF with ACR for the correction of ASD and examine intraoperative estimated blood loss (EBL), operative time, length of stay (LOS), and change in spinopelvic parameters as well as perioperative and postoperative complications.…”
mentioning
confidence: 99%
“…19,20 In our study, SVA was significantly correlated with age (r ¼ 0.285, P ¼ 0.001), maxLL (r ¼ À0.322, P < 0.001), PT (r ¼ 0.308, P < 0.001), LL-TK (r ¼ À0.500, P < 0.001), PI-LL (r ¼ 0.418, P < 0.001), and NRS (r ¼ 0.846, P < 0.001), whereas no significant correlations were observed in SVA and maxTK, SS, and PI (all P > 0.05). With the increase of patients' age, LL will be getting decreased due to the degeneration of spine, with many compensatory mechanisms involved to rebuild the sagittal balance.…”
Section: Discussionmentioning
confidence: 97%